STRATEGY TO MAXIMIZING THE USE OF COAL AND ASSOCIATED GASEOUS FUELS IN SOUTH SUMATERA BASIN - BUKIN DAULAY; DATIN F. UMAR; BINARKO SANTOSO; SUGANAL SUGANAL (Indonesian Mining Journal, 2010)
South Sumatera Basin has been known as one of the most promising sedimentary basins in Indonesia. This basin has large coal resources and is currently also believed to have an enormous amount of coalbed methane (CBM) resources. The coal seam in the basin is considerably thick and continuous, low ash and sulphur contents and could be found at favourable depth for CBM development. Coal seams can be ex- ploited by traditional mining methods, which are open cut and underground minings. When the coal seam is not economic to exploit using traditional method, underground coal gasification (UCG) technology could be implemented to optimize the use of coal and associated gaseous fuels in the basin. However, CBM operation has to be conducted before UCG operation. South Sumatera coal could be utilized for direct combustion in mine site in order to reduce transport cost; could be upgraded to obtain high calorific value coal or converted to gas, liquid and coke fuels through gasification, liquefaction and carbonization technologies.